Studi Kualitatif Pola Konsumsi Masyarakat Kota Jambi pada Bulan Ramadhan Berdasarkan Faktor Sosial - Habriyanto Habriyanto (Ekonomis: Journal of Economics and Business, 2019)
This research is related to a qualitative study relating to the consumption patterns of the Jambi city community in the month of Ramadan relating to the qualitative influence of social factors on consumption patterns. The research motive uses quality research with questionnaire data collection tools and analyzed descriptively. The results showed that the Jambi city community had made family, friends and print and electronic media as a reference in consuming during the month of Ramadan. Meanwhile the provision of consumption for Eid is largely determined by the condition of the social class in society. Then the things that shape consumption patterns in the month of Ramadan are culture such as the provision of ta`jil, preparation for Eid consumption, going home and giving gifts to relatives.